Autoimmune diseases associated with Neuromyelitis Optica Spectrum Disorders: A literature review - Shahmohammadi, Sareh; Doosti, Rozita; Shahmohammadi, Abootorab; Mohammadianinejad, Seyed Ehsan; Sahraian, Mohammad Ali; Azimi, Amir Reza; Harirchian, Mohammad Hossein; Asgari, Nasrin; Naser Moghadasi, Abdorreza (Multiple sclerosis and related disorders, 2019)
•Neuromyelitis Optica Spectrum Disorders is an autoimmune inflammatory demyelinating disease of the central nervous system.•There have been many reports on its association with other disorders including systemic and organ specific autoimmune diseases.•Here, we reviewed other immune mediated diseases associated with NMOSD and try to categorize them. Neuromyelitis Optica (NMO) is an autoimmune inflammatory demyelinating disease of the central nervous system (CNS) which predominantly involves optic nerves and spinal cord. Since the introduction of Neuromyelitis Optica Spectrum Disorders (NMOSD) as a separate entity, there have been many reports on its association with other disorders including systemic and organ-specific autoimmune diseases. Here, we reviewed other immune-mediated diseases associated with NMOSD and tried to categorize them. The present review was conducted using the PUBMED database based on papers from 1976 (i.e., since the first NMO comorbidity with SLE was reported) to 2017. We included all articles published in English. The keywords utilized included Neuromyelitis optica, Neuromyelitis Optica Spectrum Disorders, Devic's disease, in combination with comorbidity or comorbidities. Diseases with immune-based pathogenesis are the most frequently reported co-morbidities associated with NMOSD, most of which are antibody-mediated diseases. According to literature, Sjogren's Syndrome (SS) and Systemic Lupus Erythematosus (SLE) are the most frequently reported diseases associated with NMOSD among systemic autoimmune diseases. Further, myasthenia gravis in neurological and autoimmune thyroid diseases in non-neurological organ-specific autoimmune diseases are the most reported comorbidities associated with NMOSD in the literature. NMOSD may be associated with a variety of different types of autoimmune diseases. Therefore, systemic or laboratory signs which are not typical for NMOSD should be properly investigated to exclude other associated comorbidities. These comorbidities may affect the treatment strategy and may improve the patients' care and management.